Analysis of quality of service ranking for radio network optimization in Shah Alam: article / Safuan Zaini - Zaini, Safuan (2013)
Cellular technology is emerging rapidly. Based on the demand of the users, next generation cellular system is being able to provide a variety of applications for user’s satisfaction. The Universal Mobile Telecommunication System (UTMS) is a 3rd generation telecommunication system which provides various multimedia applications along with conventional telephony service. The Quality of Service (QoS) is the major concern for real time application such as voice and video telephony. Thus to fulfill the user demand, it is necessary to improve the QoS. The immediate objective of this project is to identify and rank the QoS provided by three mobile network operators; Celcom, Digi and Maxis. The QoS measured focused on an interactive class of service and based on the end-user perspective. The QoS are measure based on three parameter which are accessibility, retainability and connection or time delay. The data were collected using the Nemo Handy-A installed in a HTC Sensation Z710e smartphone. The drive tests were performed in Shah Alam. The results indicated that Maxis has the best QoS for interactive class of service in Shah Alam followed by Celcom and Digi.